Determinant Factors of Corporate Social Disclo sures in Indonesia (Issues in Social and Environmental Accounting (ISEA), 2013)
Indonesia as one of the big developing countries has been responding rapidly to the issue of Corporate Social Disclosure (CSD). This can be seen from the CSD section in the listed companies’ annual reports which keep increasing throughout the years. However, there are still inconclusive findings in factors that determine the extent of CSD. Based on a comprehensive research, therefore, this paper examines some selected factors in their relations to the extent of CSD, both quantitatively and qualitatively.  Corporate annual reports for the year 2003 to 2006 were examined to verify the CSD practices by applying a content analysis method and multiple regression analysis. Then, firm’s characteristics (category, size, financial performances, age), and group influential (creditors, auditors, owners) were analysed to seek their significant relationships to the extent of CSD. The findings show that (1) there was no significant influence of ‘company type’ to the extent of CSD; but ‘company status’ was significantly influence CSD (2) ‘company size’, ‘financial performances’, ‘age’, and ‘auditors’ influences’ were found to have significant positive influences to the extent of CSD; (3) ‘Owners’ influence’ correlated positively rather than negatively to CSD; and (4) Mixed results were provided by the ‘creditors’ influence’ throughout the years. The overall correlations between predictor and criterion variables are considered to be low to moderate, varied from 0.463 to 0.607 for correlation coefficients (R) and 0.215 to 0.368 for determinant coefficients (R2) in the regression model.